Technical efficiency and CO2 reduction potentials: An analysis of the German electricity generating sector - Stefan Seifert; Astrid Cullmann; Christian von Hirschhausen (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
In this paper, we analyze the technical efficiency of CO2 reduction potentials of German power and heat plants, using a non-parametric sequential Data Envelopment Analysis. We apply a metafrontier framework to evaluate plant-level efficiencies in the transformation of inputs into desirable (energy) and undesirable (CO2 emissions) outputs, taking into account different fossil fuel generation technologies. We dispose of a unique data set for coal-, lignite-, gas- and biomass-fired power plants from 2003 through 2010 that provides an unbalanced panel of 1459 observations. We find intra-group differences within energy generation technology, but natural gas fired power plants clearly have the highest efficiency. Furthermore, the analysis points to significant savings potentials for CO2 and fuel-input.
Keywords: L94; Q50; C14; 330; Electricity Generation; Non-parametric Efficiency Analysis; Germany; Panel 2003-1010